QT Interval Prolongation in People Treated With Bedaquiline for Drug-Resistant Tuberculosis Under Programmatic Conditions: A Retrospective Cohort Study. (1st August 2021) - Isralls, Sharon; Baisley, Kathy; Ngam, Eric; Grant, Alison D; Millard, James
Abstract: Background: Bedaquiline has a black-box warning of the risk of arrhythmias and sudden death. This study aimed to determine the incidence of QTc prolongation and cardiac events in patients receiving bedaquiline for drug-resistant tuberculosis (DR-TB) under programmatic conditions. Methods: Retrospective cohort study of patients receiving bedaquiline at a DR-TB hospital in KwaZulu Natal, South Africa from September 2017 to February 2019. The primary outcome, a prolonged QT interval corrected using the Fridericia formula (QTcF), was defined as QTcF >500 ms, QTcF change >60 ms from baseline, or both. Results: Among 420 patients (66.2% male, median age 36 years), the median QTcF was 406.4 (interquartile range [IQR], 389.1–421.3) ms at baseline, increasing to 430.5 (IQR, 414.4–445.1) ms by 3 months and 434.0 (IQR, 419.0–447.9) ms at 6 months. Eighteen of 420 patients (4.3%) had a QTcF >500 ms and 110 of 420 patients (26.2%) had a QTcF change >60 ms. There were no recorded arrhythmias or cardiac deaths. Odds of prolonged QTcF were increased with concomitant azoles (adjusted odds ratio [aOR], 5.61 [95% confidence interval (CI), 2.26–13.91]; P < .001) and an inverse association with HIV-positive status (aOR, 0.34 [95% CI, .15–.75]; P = .008) and hypertension (aOR, 0.13 [95% CI, .02–.86]; P = .02). After prolongation, the QTcF declined to <500 ms, whether drugs were interrupted or not. Conclusions: We observed a modest prolongation of QTcF, maximal at week 15; there were no recorded arrhythmias or related deaths. Abstract : A modest QTcF prolongation, maximal at 15 weeks, was observed in patients receiving bedaquiline treatment for drug-resistant tuberculosis under programmatic conditions in KwaZulu-Natal, South Africa. There were no recorded arrhythmias or related deaths.